LEAN APPLICATIONS IN AN ENGINEERING RESEARCH LABORATORY - Jamison V. Kovach; Farah M. Almatri; Elizabeth L. Lakas (International Journal for Quality Research)
Learning activities within engineering disciplines take place in both teaching and research laboratories. While Lean principles, which focus on improving process efficiency by eliminating waste (i.e., activities that do not add value), have been used previously across several disciplines to improve the efficiency of learning activities in teaching laboratories, few studies have examined the implementation of Lean practices in engineering research laboratories. This study utilized an action research approach to examine the application of Lean methods in an engineering research laboratory to address operational aspects not previously explored using Lean. The specific issues addressed include reducing both inefficiencies in staff onboarding and the occurrence of material stock outs. Lean's "respect for people" principle ensured those who do the work (lab staff) were directly involved, and action research's cyclical, iterative approach ensured learning resulting from action in one phase of the investigation was used as the input to the next phase.